Dysgraphia At Zakho University Students According to The Language : TOAL4 - Zhirwan Saeed Hajibadre (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Dysgraphia is one of the neurolinguistic diseases. Those who suffer from this disease are ordinary people who are difficult to be identified, we prepared this study as an attempt to explore the sufferers of this language disease in the University of Zakho.The study entitled “Dysgraphia at Zakho University students According to The Language (TOAL4)”. The researcher used the language test for adolescents and adults in its fourth version, it was translated from English into the Kurdish language with the approval of the residents and was applied to students of the Kurdish and Arabic language departments at the above-mentioned university for the purpose of exploring those with language disease. The study was conducted on (55) students from the second stage of the Kurdish department, and (13) of them appeared with dyslexia, besides, on (60) students from the Arabic department, and (14) of them appeared to have it. For this study, we took samples of )15(male students and (12) female students. This study was carried out according to the descriptive and statistical method (SPSS). Among the findings of the study is the presence of people with dysgraphia of both sexes in the University of Zakho. The section of the writing language of the Arabic language sample is at a bad level, while the language of pronunciation according to the gender variable in the Kurdish language sample comes in a small percentage.